EU Integrated Urban Initiatives Policy Learning and Quality of Life Impacts in Spain - Navarro Yáñez, Clemente J.; Rodríguez-García, María Jesús; Guerrero-Mayo, María José (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open-access book presents a unique interdisciplinary analysis of integrated urban initiatives promoted by the EU and their added values. This text presents a general analytical frame to study these initiatives as complex multi-level policy mixes from a comparative perspective. Cross-sectional and over-time analyses at the territorial level targeted by these initiatives are done to study the policy design, theory and impacts of urban integrated strategies. The book includes a new methodology to analyse the design and theory of urban plans (the comparative urban portfolio analysis) and quasi-experimental approaches to perform impact assessment at the neighbourhood level (the territorial target of those initiatives). Although empirical analyses focus on all local integrated plans implemented in Spain from 1994 to 2013, analytical and methodological outcomes can be applied in a broader context to analyse integral urban policies in other countries. Clemente J. Navarro. Professor, Department of Sociology, Pablo de Olavide University (Seville, Spain). Head of the Centre for Sociology and Urban Policies-The Urban Governance Lab. Jean Monnet Chair in European Urban Policies. President of the Research Committee on Community Research-International Sociological Association. His research focuses on urban sociology, policies, and governance from a comparative perspective. María J. Rodríguez-García. Senior Lecturer, Department of Sociology, Pablo de Olavide University (Seville, Spain). Member of the Centre for Sociology and Urban Policies-The Urban Governance Lab. Member of the research team of the Jean Monnet Chair in European Urban Policies. Her research focuses on the comparative analysis of local welfare systems and gender-friendly policies. María José Guerrero-Mayo. Lecturer, Department of Sociology, Pablo de Olavide University (Seville, Spain). Member of the Centre for Sociology and Urban Policies -The Urban Governance Lab. Member of the research team of the Jean Monnet Chair in European Urban Policies. Her research focused on public policy analysis and evaluation.